2019
DOI: 10.1097/cm9.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

Extralevator abdominoperineal excision versus abdominoperineal excision for low rectal cancer

Abstract: Background:Extralevator abdominoperineal excision (ELAPE) has become a popular procedure for low rectal cancer as compared with abdominoperineal excision (APE). No definitive answer has been achieved whether one is superior to the other. This study aimed to evaluate the safety and efficacy of ELAPE for low rectal cancer with meta-analysis.Methods:The Web of Science, Cochrane Library, Embase, and PubMed databases before September 2019 were comprehensively searched to retrieve comparative trials of ELAPE and APE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
2
8
0
1
Order By: Relevance
“…The mean of operative time in our study is 182.75 (range 120-300; SD = 39.157). 21 Similar results were found by the multicentre analysis of West et al which compared 176 ELAPE European colorectal surgical procedures with 124 standard APE performed at UK centres. 22 A retrospective cohort study by Carpelan et al found an insignificant difference in the rates of IOP and CRM involvement between the two groups.…”
Section: Discussionsupporting
confidence: 73%
“…The mean of operative time in our study is 182.75 (range 120-300; SD = 39.157). 21 Similar results were found by the multicentre analysis of West et al which compared 176 ELAPE European colorectal surgical procedures with 124 standard APE performed at UK centres. 22 A retrospective cohort study by Carpelan et al found an insignificant difference in the rates of IOP and CRM involvement between the two groups.…”
Section: Discussionsupporting
confidence: 73%
“…Contradictions exist on the complication rates, CRM negativity achievement and the overall survival. Recent meta-analysis evaluates these aspects [15].…”
Section: Discussionmentioning
confidence: 99%
“…The extralevator abdominoperineal excision (ELAPE) approach, described by Holm et al in 2007 [29], produces a more "cylindrical" specimen by avoidance of dissection of the mesorectum off the levators during the abdominal phase and complete (wide) excision of the levators during a prone perineal phase. A recent meta-analysis shows that ELAPE reduces IOP and local recurrence rates, without increasing perineal wound complication rates, when compared with CAPR [30]. The RELAPe randomized trial also showed no difference in complications with ELAPE, and in addition found a statistically significant reduction in CRM positivity rates, compared to non-ELAPE [31].…”
Section: Perineal Phase Techniquementioning
confidence: 99%